Serum Level of microRNA-375-3p Is Νot a Reliable Biomarker of Teratoma - BELGE, GAZANFER (In Vivo, 2020)
Background/Aim: Clinical management of testicular germ cell tumours (GCT) is based upon the measurement of serum tumour markers. Recent studies have shown that the microRNA-371a-3p is a sensitive and specific serum biomarker for all subgroups of GCT, except teratoma. To close the diagnostic gap relating to teratoma, serum levels of microRNA-375-3p have recently been suggested to represent a specific serum marker of this histological subgroup. In the present study, we tested this hypothesis. Materials and Methods: miRNA expression was analysed in serum of 21 GCT patients with teratoma, twelve patients with other GCT, and twelve male controls using the qPCR method. Results: The serum miR-375-3p levels of teratoma patients were not different from other GCT patients or controls. The ROC analysis revealed an AUC of 0.524 for the discrimination between teratoma and other pathologies. Conclusion: The miR-375-3p does probably not qualify for a useful serum biomarker to distinguish teratoma from other GCTs and from controls.